Applying and extending Oracle Spatial : a practitioner's guide on how to extend, apply, and combine Oracle's Spatial offerings with other Oracle and open source technologies to solve everyday problems /: a practitioner's guide on how to extend, apply, and combine Oracle's Spatial offerings with other Oracle and open source technologies to solve everyday problems. (2013) - Unknown
No abstract available